Rancang Bangun Teologi Sosial Gereja - Sitanggang, Pintor Marihot; Silalahi, Sylvia Wijaya (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
This article describes the constructing social theology in the ministry of the Church. In Christian teaching said that God present in the life of human being . Suffering and poverty as reality that we are facing in life. That is why theology and ministry of the Church has been faced and questioned, how God present in suffering and poverty. Choan Seng Song offers his theology, especially in the life of Asian people and proposed God present in suffering and poverty, replacing Asian culture, so the liberation and salvation from God was accepted in in their own culture. The central of theology that was developed by Song in his Suffering God theology is the liberation and salvation that has been granted by crucified Jesus Christ the Son of God. Christ as the center of liberation from God.